Recycled PVC content and particle size distribution effects on morphological and mechanical properties of expanded PVC layer for floorcoverings - Chaouch, Walid; Msahli, Slah (Comptes Rendus. Chimie)
This work deals with circular economy and sustainability. It investigates the use of recycled Polyvinyl chloride (PVC) powder as a substitute for conventional PVC resin in the expanded layer of floorcoverings without negative effects on their mechanical properties.The first challenge is to transform PVC-coated fabric waste into PVC powder completely separated from PET fibers, while simultaneously ensuring the optimal recovery of small PVC particles. Then, a comprehensive investigation focused on understanding the behavior and characteristics of recycled PVC powders. Ultimately, this research delves into the impact of varying PVC recycled content and particle sizes on the mechanical characteristics (Break Strength, Elongation at Rupture, and Tear Resistance) of the expanded PVC layer utilized in floorcovering applications. The results showed that incorporating up to 25 g (33.34% of the total PVC resin quantity) of recycled PVC demonstrated favorable mechanical performance. However, higher quantities lead to a substantial deterioration in the material’s mechanical properties, primarily due to the emergence of structural defects. To refine the amount of recycled PVC used specifically for this floorcovering application, an in-depth analysis was conducted by meticulously adjusting the particle size distribution (PSD) through a sequence of three distinct sieving processes. By achieving a PSD of recycled PVC containing particles smaller than $200~μ m$, expanded layers of satisfactory quality can be produced using up to 86.67% recycled PVC in relation to the total PVC resin quantity.